Food Security in Nigeria: Enhancing Workers’ Productivity in Precision Agriculture - Omoseni Adepoju; Oluwadamilola Esan; Oluwarotimi Akinyomi (Journal of Digital Food, Energy & Water Systems)
Food security has gained international attention in recent years and Nigeria, with its abundant human and natural resources, is not exempted from this, as improving food security requires a strong focus on agricultural development. Innovations like precision agriculture tools and other advancements in modern agriculture provide farmers worldwide with the tools and expertise to improve workers’ productivity in the agricultural sector and combat food insecurity.  This paper examined the state of food security in Nigeria and how precision agriculture enhances workers' productivity in Nigeria. The study adopted a systematic review of relevant literature on the various issues addressed in the research. The paper revealed that there is a high level of food insecurity in Nigeria, with estimates of more than 65% of the Nigerian population being food insecure, and the average productivity of Nigerian farmers is several times lower compared to farmers in a developed economy. The study revealed that precision agriculture boosts workers’ productivity by utilizing cutting-edge sensor and analysis techniques, increasing agricultural yields, and assisting management decisions which boost output, shorten labor hours, and guarantee efficient control of irrigation and fertilizer systems. Therefore, the paper recommends that Nigeria's farming sector incorporate precision agriculture equipment and technology, including drones, remote sensing, and artificial intelligence tools. Additionally, workers must be trained to use these innovative instruments and procedures to boost worker productivity and improve food security.